Glass corrosion: Sharpened interface - Putnis, Andrew (Nature Publishing Group, 2015)
The finding of a sharp interface between a chemically attacked surface and the pristine bulk in a borosilicate glass is at odds with the widely held diffusion-based mechanisms of glass durability.